Propuesta interiorista del Hotel Chalet Suisse a Apart-Hotel - González Salvador, Daniela Alejandra (2017)
Proposing an interior designer of the hotel Chalet Suisse to apart-hotel An apart-hotel is a type of hotel that offers room services different from the classical room due to their rooms suite type, that is to say that they have living room, dining room, kitchen, bedroom and bathroom, on some occasions, you can also have a study and space for washing clothes. The project is located in the Mariscal, one block from the Plaza Foch, this is an area that has plenty of restaurants, bars, hotels, shops, which is a great for grabbing the attention of tourist, and even first time backpackers. Since 2011, the casino hotel Chalet Suisse has been around for nearly 30 years, and currently the building is not being use and any format. Proposing an interior designer is to design and to establish new use for every space within the hotel, due to the abandonment of almost 6 years the interior of the building is not in ideal conditions to be inhabited. The typology of hotel will remain but will change the concept apart-hotel, creating new spaces leading users and future guests to have a pleasant stay. Demonstrating three important aspects for the design: Safety, Habitability and Functionality, resolving these aspects in the following way: A fire suppression system, will be respected and if it is necessary to strengthen the structure by ensuring the security of the guests and users within the hotel, as well as make use of renewable energies such as water harvesting and would create a system for proper disposal of waste in order to reduce the accumulation of water in the sewers of the city, finally well create ample spaces and comfortable while ensuring the comfort of users through the application of colors, textures, ergonomic furniture, Design Lighting, etc. The hotel will feature various spaces to achieve the best service, you will have: a lobby, a restaurant with a panoramic view, rooms suite with one or two rooms, single rooms, bar/nightclub, fitness center, spas, wet areas, multipurpose room, green cover accessible, stairs and elevators. The conceptualization of the project will be based on “the Ecuadorian folklore in the province of Imbabura focusing on the Otavalo culture” that will be reflected in the chromatic, decorative elements, upholstery, furniture design, etc